Effectivity of Posterior Optic Capture in Preventing Visual Axis Opacification Following Pediatric Cataract Surgery: A systematic review and meta-analysis: Doi: 10.36351/pjo.v41i1.1957 - Zahra, Raihanny Andrea; Casey, Anthea; Barliana, Julie Dewi (Pakistan Journal of Ophthalmology, 2025)
Common complication after pediatric cataract surgery is visual axis opacification (VAO). Current surgical approach commonly used today is posterior capsulotomy with anterior vitrectomy (AV), but posterior optic capturewithout AV, has been introduced as an alternative. This study reviews posterior optic capture in preventing VAO following pediatric cataract surgery.Literature searches through various databases and comprehensive analysis results in 5 selected articles. Selected studies state that optic capture is as effective as conventional methods in preventing VAO. Optic capture is a safer alternative for IOL implantation, as it results in fewer inflammatory complications and eliminates the need for AV. Hence, optic capture reduces the additional risks associated with AV.Posterior optic capture is comparable to the standard surgical approach in preventing VAO. Furthermore, it is safer in terms of inflammatory sequelae and lens epithelial cell proliferation. Optic capture presents an alluring alternative surgical approach to overcome the need for vitrectomy.